PERAN RADEN ARYA WIRARAJA DALAM PENAMAAN DESA KADUARA TIMUR DAN KADUARA BARAT - Dwiyanto, Febri; Pratikno, Ahmad Sudi (Media Bahasa, Sastra, dan Budaya Wahana, 2024)
This research wants to find out the history of naming a place in Madura. The naming of a village is closely related to the language, culture and history of the community. The naming of a village is also motivated by experiences and historical records and is also seen from the culture in the village. This research seeks to find out the origin of the names East Kaduara Village and West Kaduara Village. These villages are said to have their own history. The problem that will be raised in this study is a description of the origin of the names of the villages of West Kaduara and East Kaduara. This study uses a qualitative research method that is descriptive. The method of data collection is through observation, interviews and searching for documents containing the history of village naming. The results of interviews and observations found that the naming of East Kaduara Village and West Kaduara Village came from a resting place known as a residence which was often used as a resting place for Raden Arya Wiraraja, and the place was flanked by two opposite directions. The first direction is east, so the name of the village, East Duarah which is now known as East Kaduara Village. From the next direction, namely the west, the name of the village is West Duarah which is now known as West Kaduara Village.Keywords: East Kaduara Village; resting place; West Kaduara Village